INITIATING/SWITCHING TO INSULIN DEGLUDEC/INSULIN ASPART (IDEGASP) IN MALAYSIAN PATIENTS WITH TYPE 2 DIABETES IN REAL-WORLD SETTING - Mohamed, Mafauzy; Lim, Siang Chin; Mumtaz, Malik; Uppal, Shweta; Mukherjee, Deepak; Mohd Kassim, Mohamed Saiful; Sreedharan, Shalini; Doraiswamy, Amudha Murugan; Chong, Kuck Meng; Tat, Lu Yu; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION IDegAsp, a co-formulation of long acting basal (insulin degludec) and rapid-acting bolus (insulin aspart) insulin is used for treating patients with type 2 diabetes mellitus (T2DM) not adequately controlled by previous anti-hyperglycaemic treatments (AHTs). The current study is a subgroup analysis of the Malaysian cohort of patients from the earlier 26-week prospective, multicentre, non- interventional ARISE study that investigated the effect of IDegAsp on glycaemic control in patients with T2DM initiated or switched to IDegAsp from previous AHTs in a real world setting in six countries, including Malaysia. METHODOLOGY Adult patients (>18 years old) with T2DM using any AHTs except IDegAsp were enrolled. Patients received IDegAsp according to their physicians’ discretion. Primary endpoint was change in glycosylated haemoglobin (HbA1c) levels from baseline to end of the study (EOS, 26 weeks). RESULTS Overall, 182 out of the 205 enrolled patients (mean [SD] age: 56.4 [11.9] years) completed the study (95 men, 52.2%). Mean (SD) duration of T2DM was 11.2 (7.99) years. A total of 93 (51.1%) patients received IDegAsp once daily and 89 (48.9%) patients received twice daily at treatment initiation (mean (SD) daily dose: 29.1 [19.7] U). HbA1c levels were significantly reduced from baseline to EOS (mean [SE] estimated change from baseline: –1.3% [0.18]; p<0.0001). Consistent with this finding, FPG levels were also significantly reduced from baseline to EOS (mean [SE] estimated change from baseline: –1.8 [0.34] mmol/L; p<0.0001). The incidence of overall and nocturnal non-severe and severe hypoglycaemic events and the number of patients experiencing these events were also reduced from baseline to EOS. CONCLUSION In the Malaysian cohort, initiating or switching to IDegAsp in patients with T2DM demonstrated significant improvements in glycaemic control and numerically lower rates of non-severe and severe hypoglycaemic events.